The role of point‐of‐care tests in antibiotic stewardship for urinary tract infections in a resource‐limited setting on the Thailand–Myanmar border. Issue 10 (11th June 2015) - Chalmers, Lauren; Cross, Jessica; Chu, Cindy S.; Phyo, Aung Pyae; Trip, Margreet; Ling, Clare; Carrara, Verena; Watthanaworawit, Wanitda; Keereecharoen, Lily; Hanboonkunupakarn, Borimas; Nosten, François; McGready, Rose
Abstract Objective Published literature from resource‐limited settings is infrequent, although urinary tract infections (UTI) are a common cause of outpatient presentation and antibiotic use. Point‐of‐care test (POCT) interpretation relates to antibiotic use and antibiotic resistance. We aimed to assess the diagnostic accuracy of POCT and their role in UTI antibiotic stewardship. Methods One‐year retrospective analysis in three clinics on the Thailand–Myanmar border of non‐pregnant adults presenting with urinary symptoms. POCT (urine dipstick and microscopy) were compared to culture with significant growth classified as pure growth of a single organism >105 CFU/ml. Results In 247 patients, 82.6% female, the most common symptoms were dysuria (81.2%), suprapubic pain (67.8%) and urinary frequency (53.7%). After excluding contaminated samples, UTI was diagnosed in 52.4% (97/185); 71.1% (69/97) had a significant growth on culture, and >80% of these were Escherichia coli (20.9% produced extended‐spectrum β‐lactamase (ESBL)). Positive urine dipstick (leucocyte esterase ≥1 and/or nitrate positive) compared against positive microscopy (white blood cell >10/HPF, bacteria ≥1/HPF, epithelial cells <5/HPF) had a higher sensitivity (99% vs. 57%) but a lower specificity (47% vs. 89%), respectively. Combined POCT resulted in the best sensitivity (98%) and specificity (81%). Nearly one in ten patients received an antimicrobial to which the organism was not fully sensitive. Conclusion One rapid, cost‐effective POCT was too inaccurate to be used alone by healthcare workers, impeding antibiotic stewardship in a high ESBL setting. Appropriate prescribing is improved with concurrent use and concordant results of urine dipstick and microscopy.